Tutorials in Clinical Research: Part IV: Recognizing and Controlling Bias - Hartman, James M.; Forsen Jr, James W.; Wallace, Mark S.; Neely, J. Gail (The Laryngoscope, 2002)
Objective This is the fourth of a series of Tutorials in Clinical Research. 1–3 The objectives of this article are to heighten reader awareness of biases and of methods to reduce their impact and to provide an easy reference document for the reader during future journal reading. Study Design Tutorial. Methods The authors met weekly for 4 months discussing clinical research articles and biases for which they might be at risk. Liberal use of reference texts and specific articles on bias were reviewed. Like the example by Sackett, biases were catalogued to create an easily understood reference. Articles were chosen to demonstrate how understanding bias might facilitate assessment of the validity of medical publications. Results The article is organized into three main sections. The first section introduces specific biases. Two tables serve as rapid reference tools. The second section describes the most common biases linked to specific research approaches and reviews techniques to minimize them. The last section demonstrates the application of the information to an article in a manner that can be applied to any article. Conclusions Assessing the validity of a medical publication requires an awareness of bias for which the research is inherently at risk. A review of the publication to determine what steps the authors did or did not undertake to minimize the impact of biases on their results and conclusions helps establish the validity. This article should be of assistance in this critical review task.